Phytochemical and antioxidant potential of Bruguiera sp. fruits revealed by LC-HRMS and conventional assays - ENDAH DWI HASTUTI; SITI NUR HIDAYATI; ERMA PRIHASTANTI; MUHAMMAD LUQMAN HAKIM; SRI DARMANTI; SRI WIDODO AGUNG SUEDY (Society for Indonesian Biodiversity, 2025)
Abstract. Hastuti ED, Hidayati SN, Prihastanti E, Hakim ML, Darmanti S, Suedy SWA. 2025. Phytochemical and antioxidant potential of Bruguiera sp. fruits revealed by LC-HRMS and conventional assays. Biodiversitas 26: 5714-5725. Almost all mangrove fruits contain phytochemicals and nutrients, exhibiting varying levels of antioxidant activity that help them adapt to extreme environmental conditions. This study aims to investigate the phytochemical profile, nutrient composition, and antioxidant activity of Bruguiera sp. mangrove fruit through qualitative and quantitative analyses. Qualitative analysis was performed using High-Resolution Liquid Chromatography-Mass Spectrometry (LC-HRMS) to analyze the phytochemical profile. Quantitative analysis included determining nutrient composition using gravimetry, the Kjeldahl method, and the by-difference method. Secondary metabolites and pigments were analyzed using spectrophotometric analysis and High-Performance Liquid Chromatography (HPLC). Antioxidant activity was determined through the 2,2-diphenyl-1-picrylhydrazine (DPPH) assay. The results showed that Bruguiera sp. fruits contained lipids (28%), flavonoids (10%), alcohols (8%), carbohydrates (8%), and esters (8%) as the five most abundant groups of compounds that play a role in adaptation to a highly saline environment. In addition, its adaptability is also demonstrated by its high phenol concentrations (11.2% w/w) and significant levels of chlorophyll b (9.77 mg/g). The nutrient composition indicated a high carbohydrate content (79.21% w/w), carotenoids (17.61 ?mol/g), and vitamin C (15.68 mg/kg). The integration of LC-HRMS with conventional methods improves the identification of bioactive compounds. Antioxidant analysis demonstrated very strong activity (0.19 ppm), indicating potential antioxidant activity. These findings indicate that the Bruguiera sp. fruit is a promising natural source of antioxidants with significant potential as a functional food and valuable medicinal source. The strong antioxidant properties of this fruit contribute to the prevention of diseases associated with oxidative stress and provide a sustainable nutritional alternative, especially in areas with limited access to nutritious foods.